The Christian past that wasn't : debunking the Christian nationalist myths that hijack history - Throckmorton, Warren (Broadleaf Books, 2026)
"Bad history is useful to those who circulate it. In The Christian Past That Wasn't, Warren Throckmorton challenges seven myths that prop up the illusion that the United States was founded as a Christian nation. It's never been more important to understand why myths about the past wield so much psychological force and who those myths empower"-- Provided by publisher.